Analysis of chitin-binding proteins from Manduca sexta provides new insights into evolution of peritrophin A-type chitin-binding domains in insects. (July 2015) - Tetreau, Guillaume; Dittmer, Neal T.; Cao, Xiaolong; Agrawal, Sinu; Chen, Yun-Ru; Muthukrishnan, Subbaratnam; Haobo, Jiang; Blissard, Gary W.; Kanost, Michael R.; Wang, Ping
Abstract: In insects, chitin is a major structural component of the cuticle and the peritrophic membrane (PM). In nature, chitin is always associated with proteins among which chitin-binding proteins (CBPs) are the most important for forming, maintaining and regulating the functions of these extracellular structures. In this study, a genome-wide search for genes encoding proteins with ChtBD2-type (peritrophin A-type) chitin-binding domains (CBDs) was conducted. A total of 53 genes encoding 56 CBPs were identified, including 15 CPAP1s (cuticular proteins analogous to peritrophins with 1 CBD), 11 CPAP3s (CPAPs with 3 CBDs) and 17 PMPs (PM proteins) with a variable number of CBDs, which are structural components of cuticle or of the PM. CBDs were also identified in enzymes of chitin metabolism including 6 chitinases and 7 chitin deacetylases encoded by 6 and 5 genes, respectively. RNA-seq analysis confirmed that PMP and CPAP genes have differential spatial expression patterns. The expression of PMP genes is midgut-specific, while CPAP genes are widely expressed in different cuticle forming tissues. Phylogenetic analysis of CBDs of proteins in insects belonging to different orders revealed that CPAP1s from different species constitute a separate family with 16 different groups, including 6 new groups identified in this study. The CPAP3s are clustered into a separate family of 7 groups present in all insect orders. Altogether, they reveal that duplication events of CBDs in CPAP1s and CPAP3s occurred prior to the evolutionary radiation of insect species. In contrast to the CPAPs, all CBDs from individual PMPs are generally clustered and distinct from other PMPs in the same species in phylogenetic analyses, indicating that the duplication of CBDs in each of these PMPs occurred after divergence of insect species. Phylogenetic analysis of these three CBP families showed that the CBDs in CPAP1s form a clearly separate family, while those found in PMPs and CPAP3s were clustered together in the phylogenetic tree. For chitinases and chitin deacetylases, most of phylogenetic analysis performed with the CBD sequences resulted in similar clustering to the one obtained by using catalytic domain sequences alone, suggesting that CBDs were incorporated into these enzymes and evolved in tandem with the catalytic domains before the diversification of different insect orders. Based on these results, the evolution of CBDs in insect CBPs is discussed to provide a new insight into the CBD sequence structure and diversity, and their evolution and expression in insects. Graphical abstract: Highlights: 53 genes encoding 56 ChtBD2-containing chitin-binding proteins were found in Manduca sexta . CPAPs appeared and diversified prior to the evolutionary radiation of insect species. Apparition and multiplication of chitin-binding domains in PMPs is species-specific Chitin-binding domains in PMPs appeared after the diversification of insects. Chitin-binding domains in CHT and CDAs evolved with the catalytic domains. Chitin-binding domains in CHT and CDAs appeared before the diversification of insects.